Analysis of Earnings Management in Cosmetics and Household Sub-Sector Companies - Iwan Suhasto; Shinta Anggraeny; Dewi Kirowati (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
Every company was founded with the aim of making a profit and maximizing the company's wealth. This study aims to determine the company's earnings management. Earnings management is an option used by company managers in meeting the company's needs in terms of improving performance by regulating company profits for a certain period. Profit is an important component in performance appraisal. The financial report contains a description of management's performance which then becomes the basis for determining investment. The object of research is the cosmetics and household needs sub-sector companies listed on the IDX. The method used as the basis for calculating earnings management is using the Healy model in the 2015-2019 financial statements. The Healy model is a fairly simple earnings management calculation model performed by comparing the average total accruals divided by the total accruals of the previous period. The data used is secondary data obtained from the IDX official website. Data collection techniques in this study using literature study. The data analysis technique used begins with collecting data in the form of financial statements and calculating descriptive accruals. The calculation results are used as the basis for earnings management analysis.